The political economy of schooling in Cambodia : issues of quality and equity - Kitamura, Yuto (Houndmills, Basingstoke, Hampshire ; New York, NY : Palgrave Macmillan, 2016)
"The Political Economy of Schooling in Cambodia presents a detailed portrait of the education system in Cambodia. In addition to contextualizing the development of education in Cambodia from a long-term historical perspective, the book addresses issues such as: the local enactment of student-centered pedagogies, the lived experiences of students and teachers, challenges to achieving literacy and numeracy, practices of private tutoring, the rise of education-related civil society and its influence on education policymaking, issues around student dropout, and current themes in higher education and teacher education. This breadth of issues is addressed through recent quantitative and qualitative analyses by scholars long engaged in research in Cambodia. The book's focus on challenges accompanying Cambodia's continued expansion and modernization of its education system makes the findings and lessons presented relevant both within and beyond Cambodia"--
"The Political Economy of Schooling in Cambodia offers an in-depth look at education in Cambodia to date. The volume examines a variety of key issues of high relevance to Cambodia and other developing countries as they expand their education systems and grapple with challenges to providing a quality and equitable education"--
Machine generated contents note: -- 1. Introduction; Chhinh Sitha, D. Brent Edwards Jr., James H. Williams, and Yuto Kitamura PART I: CONTEXT 2. The Backstory of Education in Cambodia; Takayo Ogisu and James H. Williams 3. Getting to the Decision-Making Table in Educational Governance: The Emergence of Cambodian Civil Society within the 'New Global Geometry of Power'; D. Brent Edwards Jr. and William C. Brehm PART II: SCHOOLS 4. Pedagogy in Cambodian Schools: A Logic that Governs Teaching and Learning; Takayo Ogisu 5. Policy Intention versus Policy Implementation: Disparities in Equity and Diversity in Inclusive Education in Cambodia; Makiko Hayashi and D. Brent Edwards Jr. 6.The Structures and Agents Enabling Educational Corruption in Cambodia: Shadow Education and the Business of Examinations; William C. Brehm PART III: DROPOUT 7.Does Students' Gender Matter? Parents' Educational Expectations, Their Determinants and Consequences in Explaining Students' Dropout in an Area in Cambodia; Thomas Zimmermann and James H. Williams 8.The Complexity of Continuation: A Narrative Perspective on Student Transition and Dropout from Primary to Lower Secondary School in Cambodia; D. Brent Edwards Jr., Thomas Zimmermann, Chhinh Sitha, James H. Williams, and Yuto Kitamura PART IV: HIGHER EDUCATION 9. Higher Education in Cambodia: Expansion and Quality Improvement; James H. Williams, Yuto Kitamura, and C. Sopcheak Keng 10. Who Wants to Teach in Cambodia?; James H. Williams, Yuto Kitamura, Takayo Ogisu, and Thomas Zimmermann 11. Quality of Education and Research in Cambodian Higher Education Institutions; Yuto Kitamura, Naoki Umemiya, Yasushi Hirosato, and Sam Sideth Dy PART V: CONCLUSION 12. The Way Forward for Education Reform in Cambodia; Chhinh Sitha.
Includes bibliographical references and index.
Keywords: Education and state -- Cambodia; Education -- Standards -- Cambodia; Education -- Aims and objectives -- Cambodia; Cambodia